Thrombin generation in children using ThromboScreen reagent kit with ST Genesia—A pilot study. (29th July 2021) - Gassiot, Susanna; Ruiz‐Llobet, Anna; Suleman, Warda; Sarrate, Edurne; Berrueco, Ruben
Abstract: Introduction: Thrombin generation assays assess overall coagulation system and are widely used in research; however, they still need standardization and clinical validation. The new ST Genesia is a benchtop, automated analyzer that normalizes each thrombin generation parameter using a reference plasma. The ThromboScreen reagent kit has two triggers, one of which contains thrombomodulin to assess the effect of the protein C pathway. This study aimed to make a pilot approach to the ThromboScreen reference range in children and evaluate the impact of sex, age, and pro‐ and anticoagulant plasma proteins on thrombin generation parameters. Methods: This study included 55 healthy children from the following age groups: 1‐6 years (n = 14), 7‐11 years (n = 15), and 12‐17 years (n = 26). Children younger than 1 year were excluded from the study. We measured thrombin generation using ThromboScreen, coagulation routine and test, pro‐ and anticoagulant proteins. Results: Age did not influence ThromboScreen results. Males showed significantly lower endogenous thrombin potential and peak height values than females. The strongest determinants of endogenous thrombin potential were von Willebrand factor parameters, whereas for endogenous thrombin potential inhibition, the strongest determinants were protein C and protein S. No statistically significant differences were found between groups on temporal parameters. Conclusions: For the ThromboScreen reagent kit, it may not be necessary to subdivide reference ranges according to age for children (>1 year).